The physiology of judo-specific training modalities - Franchini, E.; Brito, C. J.; Fukuda, D. H.; Artioli, G. G. (The Journal of Strength and Conditioning Research, 2014)
Understanding the physiological response to the most common judo training modalities may help to improve the prescription and monitoring of training programs. This review is based on search results using the following terms: "judo," "judo and training," "judo and physiology," "judo and specific exercises," and "judo and combat practice." Uchi-komi (repetitive technical training) is a specific judo exercise that can be used to improve aerobic and anaerobic fitness. Effort to pause ratio, total session duration, number and duration of individual sets, and the type of technique can be manipulated to emphasize specific components of metabolism. "Nage-komi" (repetitive throwing training) can also be used to improve aerobic and anaerobic fitness, depending on the format of the training session. "Randori" (combat or fight practice; sparring) is the training modality most closely related to actual judo matches. Despite the similarities, the physiological demands of randori practice are not as high as observed during real competitive matches. Heart rate has not shown to be an accurate measure of training intensity during any of the previously mentioned judo training modalities. High-volume, high-intensity training programs often lead judo athletes to experience overtraining-related symptoms, with immunosuppression being one of the most common. In conclusion, judo training and judo-specific exercise should be manipulated to maximize training response and competitive performance.